Vida Saludable: Anote su presión sanguínea - Leigh Ann Martin (EDIS)
Revised! FCS8601Span, a 1-page handout by Leigh Ann Martin, is the Spanish language version of FCS8601 Healthy Living: Keep Track of Your Blood Pressure. It provides a convenient table for recording blood pressure readings for better blood pressure management. Published by the UF Department of Family Youth and Community Sciences, October 2009.